Development of a method for determining acid -degree value of oil contained in sunflower phospholipids on the basis of the NMR method - E. P. Victorova; O. S. Agafonov; S. M. Prudnikov; T. A. Shakhray; I. I. Ukrayintseva (Новые технологии, 2018)
It’s been determined that the amplitude of the NMR signals of protons of the solid phase, that is, the amplitude of NMR signals of soap protons (Am), is an analytical parameter characterizing the content of the soap formed, and, consequently, the content of free fatty acids. It’s been revealed that there is a linear dependence between the acid-degree value of oil extracted from sunflower phospholipids and the amplitude of NMR signals of soap protons, which is described by the following equation: A.n.=0,2481× Ам+ 0,4319. A method has been developed for determining one of the main quality indicators of sunflower phospholipids-the acid-degree value of oil extracted from sunflower phospholipids, using the nuclear-magnetic relaxation method, which makes it possible to eliminate the use of toxic solvents, as well as to improve the accuracy of the analysis results.